An Overview of E-Learning in Nursing Students at the Institute of Technology and Health Bali - Putu Inge Ruth Suantika; Ni Made Manik Elisa Putri; Sarah Kartika Wulandari (KHD-Production, 2022)
For more than a year the teaching and learning process has changed patterns to online to avoid the increasingly widespread spread of the covid 19 virus. This certainly encourages students to be able to adapt to the teaching and learning process. Because of this change in learning model, facilities and infrastructure are needed as well as methods that resemble the face-to-face teaching and learning process. Many students find it difficult to participate in the online learning process due to various factors, both internal and external. to describe online learning for third-level nursing students at ITEKES Balli. This study uses a descriptive cross sectional design with a sample of students at ITEKES Bali semester VI. The type of sampling is total sampling. The analysis used is univariate analysis. The results of the study were 86 people (457%) said it was quite easy to understand the material, 78 people (41.5%) said it was enough to interact both with friends and with teachers, 76 people (40.4%) said the use of online learning methods was quite effective. and 90 people (47.9%) said they were quite independent during the online learning process. of all aspects studied in e-learning learning are classified as sufficient.